2020
DOI: 10.3390/ijerph17030797
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Fitness Level and Gross Motor Skills of 4–6-Year-Old Chilean Children

Abstract: In childhood, fitness level is considered an important indicator of health, while gross motor skills are the basis of future motor competence. So far, no reference values have been found for the Chilean population. Therefore, this study aims to provide fitness level and gross motor skill reference values by gender and age of Chilean children aged 4–6 years. A cross-sectional analysis was conducted that included 728 children between 4 and 6 years old from the La Araucanía region of Chile. To assess the fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Bibliometric statistics were carried out according to the country of origin (Table 2 ) and the year of publication ( Figure 2 ), respectively. As shown in Table 2 , of the 76 literatures examined, 54 (71.1%) were from Europe ( 14 , 20 72 ), 16 (21.0%) from Asia ( 73 88 ), and 6 (7.9%) from the Americas ( 89 94 ). As shown in Figure 2 , most studies on the physical fitness of preschool children were published after 2011 and accounted for 68 (89.5%) of the total inclusions, especially after 2015, there are more than six publications per year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric statistics were carried out according to the country of origin (Table 2 ) and the year of publication ( Figure 2 ), respectively. As shown in Table 2 , of the 76 literatures examined, 54 (71.1%) were from Europe ( 14 , 20 72 ), 16 (21.0%) from Asia ( 73 88 ), and 6 (7.9%) from the Americas ( 89 94 ). As shown in Figure 2 , most studies on the physical fitness of preschool children were published after 2011 and accounted for 68 (89.5%) of the total inclusions, especially after 2015, there are more than six publications per year.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing FITness in PREschoolers (PREFIT) ( 14 ) includes seven test items covering three health-related (body composition, cardiovascular fitness, and muscular strength) and three skill-related components (agility-speed, power, and balance). PREFIT is widely used in eight countries: Spain (n = 11) ( 14 , 20 – 28 , 72 ), Sweden (n = 6) ( 29 32 , 65 , 66 ), China (n = 1) ( 73 ), Estonia (n = 1) ( 36 ), Norway (n = 1) ( 33 ), Italy (n = 1) ( 37 ), Chile (n = 1) ( 89 ), Turkey (n=1) ( 88 ), and Serbia (n = 1) ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that this intervention did not improve flexibility in preschool children, which was similar to the findings of Macak et al [ 26 ]. Studies showed that flexibility decreased with age, and this decline was caused not only by aging-related changes but also by a lack of training in this flexibility, which can be maintained or improved by training in specific ways [ 29 , 30 ]. Therefore, this study did not report that the possible reason for the improvement in preschool children's flexibility was due to the inclusion of less relevant exercises while designing the activities, which also needs to be improved in future research.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] In Latin America, Brazil developed a fit-for-purpose PF test battery 21 that has thus far only been used to assess Brazilian youth. In other Latin American countries, PF has been reported using different test protocols, [22][23][24][25][26][27] which makes between-country comparisons challenging. Furthermore, international surveillance efforts such as Active Healthy Kids Global Alliance's Global Matrix 3.0 initiative, has identified the paucity of available data, and the need for up-to-date information on the PF levels of Latin American youth.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%